Survey on the Avian Diversity along the Annapurna Sanctuary Trekking Route in Western Nepal (ZOO-Journal, 2019)
A bird survey was carried out on one of Nepal’s most popular trekking destinations, Annapurna Base Camp in the Annapurna Conservation Area (ACA). ACA trekking route was selected as our transect line. Direct observation method and call count method were used during the survey following the transect line. A total of 166 species were recorded representing nine orders and 39 families. The main objective of the present work was to study the avian diversity. Eight nationally threatened and three globally threatened bird species were recorded during the survey. White-rumped vulture Gyps bengalensis (Gmelin) and Red-headed vulture Sarcogyps calvus (Scopoli) (critically endangered species) were also recorded. The abundancy of Rufous sibia Malacias capistratus (Vigors) was higher, while Nepal house martin Delichon nipalense (Moore) had the highest number. Hunting, excessive harvesting of bamboo shoots, orchids, overgrazing and improper management of solid waste were directly observed threats.